ANALISIS FAKTOR PRODUKSI NELAYAN ALAT TANGKAP PAYANG DI KABUPATEN PADANG PARIAMAN PROVINSI SUMATERA BARAT - ., Tashwir; Kamal, Eni; sarianto, deni; Fitri, Yulia; ., Harminto; Yeka, Adnal (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2021)
It is hoped that the use of payang fishing gear can help increase the catch of fishermen who will help improve the welfare of the fishing community. The purpose of this study was to analyze the factors of production of payang fishing gear fishermen in Sungai Limau District, Padang Pariaman Regency. The research was conducted in Padang Pariaman District, namely in Sungai Limau District, the respondents in this study were full fishermen who had payang fishing gear as many as 21 fishermen and ABK sampling of 2 people each. When the study was conducted for 2 (two) months early November to the end of December 2019. This type of research used in this research is quantitative descriptive method research. The results of the analysis show that overall the factors of production, namely the trip trip factor, the amount of fuel, the number of crew members, the length of the wings, the size of the ship's engine, the setting and the institutional and policy influence on production with an F count of 28,352 2.83 on the successful production of payang fishermen's catches. In Sungai Limau District, Padang Pariaman Regency. 90.5% of payang fishermen's catch production can be explained by these factors, while 9.5% is influenced by other tractors not included in the analysis. The factor of the amount of fuel with a t count of 4.523 1.761 and the number of ABK with a t count of 3.246 1.76131 are two main factors that have a significant positive effect on the production of Payang fishermen's catches in Sungai Limau District, Padang Pariaman Regency.